Coffee + COVID: people, place, and pandemic. Issue 2 (15th March 2021) - Patch, Jason; Heeks, Amberjean; Luppino, Kristen; Nims, Mikala; Ortiz, Molly; Presutti, Keryn; Reid, Chelsea
Abstract : This project consisted of ethnographic and visual fieldwork studying four coffee shops during the COVID-19 pandemic. Research focused on spatial reconfiguration for health considerations and customer actions in response. We observed what we identify as modified normalcy. The images in this essay illustrate our findings on entering potentially unsafe spaces, managing the flow of customers, limited efforts at contact tracing, modified seating arrangements, and new expectations for customers. We find that there is a default to create seemingly safer, but still comfortably distinct places for consumption and social interactions.